Multiple disadvantages: class, social capital, and well-being of ethnic minority groups in the UK during the COVID-19 pandemic - Li, Yaojun; Ding, Lin (Frontiers in Sociology, 2024)
Introduction The COVID-19 pandemic has caused untold damage to the socio-economic lives of people all over the world. Research has also demonstrated great inequality in the pandemic experience. In the UK as in many other countries, people from ethnic minority backgrounds and in working-class positions have suffered disproportionately more than the majority group and those in salariat positions in terms of income loss, financial difficulty, and vulnerability to infection. Yet little is known about how people coped in the daily lives and tried to maintain their well-being during the most difficult days of the pandemic through social capital. Methods In this paper, we draw data from the COVID-19 Survey in Five National Longitudinal Studies to address these questions. The survey covered the period from May 2020 to February 2021, the height of the pandemic in the UK. It contains numerous questions on contact, help and support among family, friends, community members, socio-political trust, and physical and mental health. We conceptualise three types of social capital and one type of overall well-being and we construct latent variables from categorical indicator variables. We analyse the ethnic and socio-economic determinants of the three types of social capital and their impacts on well-being. Results Our analysis shows that social capital plays very important roles on well-being, and that ethnic minority groups, particularly those of Pakistani/Bangladeshi and Black heritages, faced multiple disadvantages: their poorer socio-economic positions prevented them from gaining similar levels of social capital to those of the white group. However, for people with the same levels of social capital, the effects on well-being are generally similar. Discussion Socio-economic (class) inequality is the root cause for ethnic differences in social capital which in turn affects people’s well-being.